Simulation, parameter identification and control system design of an aircraft using unified mathematical model. - Muhammad, Hari
This paper discusses the role of mathematical model of an aircraft dynamics in flight mechanics
Keywords: Control system design; Flight simulation; Mathematical model; Parameter identification; UAV